The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1111/roiw.12341
|View full text |Cite
|
Sign up to set email alerts
|

Housing and Health

Abstract: Deprived housing is recognized as a source of poor health, but there is still little evidence of a causal relationship between housing and health. While existing literature identifies neighborhood effects and the individual dwelling as factors which affect health, it does not offer a joint examination of these factors. Moreover, endogeneity is a concern in analyses of both problems. Thus far, studies addressing endogeneity have done so through experimental design or instrumental variables. The first approach s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…They not only live in extreme poverty, but also suffer from high levels of family and social disengagement, have great difficulty in achieving social/employment reintegration, and suffer from significant mental and physical health problems (Panadero and Vázquez 2016). A lack of housing is a significant determinant factor in health (Angel and Bittschi 2019). Several studies have reported that homeless people are in poorer physical health than the general population (Lebrun-Harris et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…They not only live in extreme poverty, but also suffer from high levels of family and social disengagement, have great difficulty in achieving social/employment reintegration, and suffer from significant mental and physical health problems (Panadero and Vázquez 2016). A lack of housing is a significant determinant factor in health (Angel and Bittschi 2019). Several studies have reported that homeless people are in poorer physical health than the general population (Lebrun-Harris et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Poor living conditions are often associated with poor health [15,16]. Substandard housing including lack of safe drinking water, sanitary water for cooking, effective garbage disposal devices, overcrowding, and poor ventilation has been confirmed to be closely related to the spread of respiratory infectious diseases [17,18].…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…As the largest developing country, China has the largest population in the world and is actively implementing measures for the renovation and governance of residential space to improve living conditions as part of the implementation of a healthy China strategy. Thus, China is a very important of 15 area for research on housing and health. This study used data from the China Family Panel Study in 2018 to examine the impact of living conditions on residents' self-rated health and to determine the impact mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…One major social determinant of this wellbeing is housing [ 8 ], a primary contributor to achieving SDGs, especially SDG 3 [ 9 ]. Nevertheless, despite a large body of literature on the housing–health linkage in developed regions such as the United States [ 10 , 11 , 12 ], Europe [ 13 , 14 , 15 , 16 , 17 , 18 , 19 ], New Zealand [ 20 , 21 ], and Australia [ 22 , 23 , 24 ], evidence in developing countries remains scarce. Housing remains one of the most understudied aspects of aging in China [ 25 ].…”
Section: Introductionmentioning
confidence: 99%